Pengaruh Media Googgle Sites Terhadap Hasil Belajar Peserta Didik Materi Pengetahuan Dasar Geografi Di Kelas X SMA Negeri 3 Gorontalo Utara - Batdi, Fazli; Pratama, M. Iqbal Liayong; Masruroh, Masruroh (-, 2025)
This study aims to determine the effect of Google sites media on student learning outcomes, provide experimental treatment to students to see if there is an effect on learning outcomes. This study is an experimental type of research and uses a quasi-experimental method, quasi-experiment is one type of experimental research that is close to a real experiment, research used to find the effect of certain treatments on others in controlled conditions. This research was conducted at SMA N 3 Gorontalo Utara, At the implementation stage the research subjects were divided into two classes, namely the control and experimental classes, the control class consisted of 34 students and the experimental class consisted of 32 students. There is an effect on student learning outcomes using Google sites media, namely by looking at the Hypothesis test value, the experimental class value, significant (sig) 0.00 0.05. So there is an effect of Google sites media on the learning outcomes of students at SMA N 3 Gorontalo Utara.